2014
DOI: 10.1016/s2095-3119(13)60521-3
|View full text |Cite
|
Sign up to set email alerts
|

Seed Priming Influence on Early Crop Growth, Phenological Development and Yield Performance of Linola (Linum usitatissimum L.)

Abstract: Reduced early crop growth and limited branching are amongst yield limiting factors of linola. Field response of seed priming treatments viz. 50 mM salicylic acid (SA), 2.2% CaCl2 and 3.3% moringa leaf extract (MLE) including untreated dry and hydropriming controls was evaluated on early crop growth and yield performance of linola. Osmopriming with CaCl2 reduced emergence time and produced highest seedling fresh and dry weights including Chl a contents. Osmopriming with CaCl2 reduced crop branching, flowering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
17
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 17 publications
7
17
0
2
Order By: Relevance
“…This diverse composition of MLE indicates that this extract can be used as a plant biostimulant. Many researches highlighted MLE role to improve plant growth and development in different crops (Yasmine et al, 2012;Rady et al, 2013;Rehman et al, 2014), which is also evident from results of the present study. Improved seedling growth traits i.e.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This diverse composition of MLE indicates that this extract can be used as a plant biostimulant. Many researches highlighted MLE role to improve plant growth and development in different crops (Yasmine et al, 2012;Rady et al, 2013;Rehman et al, 2014), which is also evident from results of the present study. Improved seedling growth traits i.e.…”
Section: Discussionsupporting
confidence: 85%
“…Like other biostimulants, the potential of MLE when applied through seed or plant foliage have been shown to improve the plant tolerance to abiotic stresses, including salinity (Yasmeen et al, 2013;Rady et al, 2013;Howladar, 2014). These reports and others have been shown that MLE application improved crop performance, resulting from vigorous seedling growth, maintained optimum tissue water status, improved membranes stability, enhanced antioxidant levels and activated plant defense system, increased levels of plant secondary metabolites, reduced uptake of undesirable Na + and/or Cl − , and enhanced shoot or leaf K + (Yasmeen et al, 2012;Rehman et al, 2014). The MLE act at low or even diluted concentration of 1:30, and the chemical composition of this extract may vary with species, season of collection and extraction procedure used.…”
Section: Introductionmentioning
confidence: 94%
“…3,4 Generally, seed priming has been successfully demonstrated to improve the rate and uniformity of seedling emergence in many crops, particularly vegetables, cereals and oilseed crops. [5][6][7][8] Hydro-priming in rice improved germination percentage, enhanced subsequent seedling growth resulting in higher grain yield in dry direct-seeded rice. 9 At the subcellular level, seed priming was found to improve germination and seedling vigor by conferring protection to cellular proteins, 10 repairing DNA damage during seed storage, 11 improving the functioning of protein synthesis machinery 12 and increasing energy status by improving mitochondrial integrity.…”
Section: Introductionmentioning
confidence: 99%
“…Exogenously applied MLE through seed or plant foliage is found to improve germination, seedling growth and productivity in many crops under normal and stress conditions (Basra et al 2011;Yasmeen et al 2012Yasmeen et al , 2013aRehman et al 2013). Such improvements in plant productivity are related to greater leaf area, alteration in source-sink relationship and delayed senescence.…”
Section: Introductionmentioning
confidence: 99%